Pemphigus scoring systems and their validation studies - A review of the literature - Darby Boucher; Anna Wilson; Dedee F Murrell (Wolters Kluwer Medknow Publications, 2023)
Pemphigus is a rare autoimmune blistering disease that affects the skin and mucous membranes. Despite recent advances in treatment, pemphigus is associated with high patient mortality and has a significantly negative impact on patients' quality of life and mental health. Validated scoring systems to accurately measure pemphigus severity are vital for the monitoring of disease activity, evaluation of treatment efficacy and trialing, comparison and introduction of new treatments. This article reviews the existing scoring systems for pemphigus and their validation studies and proposes a future area of research regarding global assessments for simplistic scoring of pemphigus severity.